Field analysis of the deterioration after some years of use of four insect-proof screens utilized in Mediterranean greenhouses - A. López-Martínez; D. L. Valera-Martínez; F. D. Molina-Aiz; A. A. Peña-Fernández; P. Marín-Membrive (Spanish Journal of Agricultural Research, 2013)
The installation of insect-proof screens on greenhouse vents is one of the principal methods of protection against harmful insects for crops. Their main disadvantage lies on their negative effects on natural ventilation and greenhouse microclimate, which have been the focus of studies by several authors. However, few works have analysed the effect of accumulated dust and dirt on these screens. The present study has analysed four anti-insect screens, comparing their geometric characteristics before installation and after three to four years of use. Two negative effects have been observed and quantified: deterioration of the threads that make up the screen and reduction of porosity due to accumulated dirt in the pores. This deterioration over time gives leads to a mean increase in thread diameter of 3.1%, as well to a mean decrease in the pore size of 6.2% and 2.3% in the weft (Lpx) and the warp (Lpy), respectively. In fact, the insect-proof screen porosity (φ) decreased due to the deterioration of the threads by an average of 6.5%, in addition to an average 20.3% reduction due to the accumulation of dirt in the pores, making a total reduction in porosity of 26.8%. This decrease in porosity leads to lower greenhouse ventilation rates, and is therefore detrimental for the greenhouse microclimate. Consequently, it is recommended that insect-proof screens in arid areas such as Almería (Spain), with abundant dust suspended in the atmosphere, be washed monthly using water sprayed at high pressure.